The Role of Canadian Colleges and Technical Institutions in International Education: A 40-Year Perspective - Hurabielle, Jacques P. E.; Grace, Michael G. A.; Andrews, Michael (Alberta Journal of Educational Research, 2002)
This article documents the emergence and evolution of Canadian postsecondary technical or vocational international education by analyzing information derived from the administration of an in-depth survey to senior college officials in Canadian colleges and postsecondary technical or vocational institutions. Those who responded on behalf of the appropriate department in each institution had a wide variety of education, training, and skills related to the promotion and enhancement of international education. Results showed that the primary goals of international education in these institutions since 1960 were to form human capital, promote economic growth, and facilitate economic globalization. Few institutions in Canada in 1960 met the criteria of being colleges or technical institutions, and even fewer were involved in international education. The large increase in their numbers a few years later coincided with a rapid expansion of interest in international education. Geographical areas of international education were concentrated in Africa, Southeast Asia, and the Caribbean from 1971 to 1985. From 1986 to 1998 this changed to cover almost every area of the nonindustrialized world. The intent of international education in these institutions changed from the earlier altruism to a focus on staff development, generation of revenue, and provision of humanitarian assistance. This information may be of assistance to institutions setting policy and suggesting strategies for more effective coordination of international education.